Option Strategies : Profit-Making Techniques for Stock, Stock Index, and Commodity Options. - Smith, Courtney, 1952- (John Wiley & Sons, 2008)
Updated and revised to include a decade of growth in the scope and complexity of options, Options Strategies: Profit-Making Techniques for Stock, Stock Index, and Commodity Options, 3rd Edition is a comprehensive guide to options trading strategies written in clear, non-technical language. In addition to insight into options issues like carrying changes, strike prices, commissions, interest rates, and break-even points, new chapters show how to predict the direction of implied volatility. Accessible examples, charts, and graphs will help you obtain the information you need to succeed in the hi.